O ensino de trompa a partir dos manuscritos do método treinos funcionais para trompa de Adalto Soares - Pinto, Renato Barbosa (2021)
The objective of this research is to analyze the technical and methodological characteristics contemplated by the manuscripts of the didactic material developed by Adalto Soares, entitled “Functional Training for Horn” (January 2021 version). In this way, aims to contribute to the development of the research about the Horn, more specifically on didactic materials. This area, in general, has shown significant growth in recent decades, but it still needs to be developed, especially when we consider the Brazilian scenario. The specific goals are: to understand the process of creating and developing the material; to identify methodological approaches intrinsic to the material; observe how the various horn techniques and theoretical-musical foundations are covered; verify possibilities of approaches based on concepts defined in the investigated literature; and describe contents from conceptions presented by the author and relate them to parameters observed in the studied bibliography. The research was constituted from the analysis of the didactic material and presents a qualitative research method, in which the methodological nuances used in the conception, the subsequent development of the material and the technical questions present in the exercises were verified. The analysis of the material, together with semi-structured interviews and classroom observations provided the necessary data, which after its organization, were crossed with the theoretical framework, which generated the research results. From the interviews and observations, it was possible to perceive how the material is organized and applied by the author, the contents covered, the importance as a reference for the national scenario, in addition to the main didactic characteristics that stand out in the used approach.